The Synergy of Talking Stick Strategy and Motivation in Developing Senior High School Students’ Speaking Proficiency - Rio Ahmad Wildan; Darmawan Budiyanto; Heru Setiawan (Yayasan Corolla Education Centre, 2026)
This study was aimed to find out: (1) whether or not there was significant difference on students’ speaking skill between the students who were taught by using talking stick strategy and those who were taught by using lecturer strategy, (2) whether or not there was significant difference on students’ speaking skill between motivated students and unmotivated students, 3) whether or not there was any effect of interaction between talking stick strategy and motivation on speaking skill. The study used a factorial design with a population of 400 tenth-grade students of SMA NEGERI 11 Palembang in the 2024-2025 school year. There were 62 students in the sample, 31 students in the experimental group, and 31 students in the control group. The analysis of the data revealed a significant difference in speaking skills, as evidenced by the result of the Independent Samples T-Test, in which the significance value (0.001) was less than α (0.05). This indicated an improvement in students' speaking skills. However, the Two-Way ANOVA results showed that students’ motivation by itself did not have a significant impact, with a significance value (.696) Interestingly, the interaction between the Talking Stick strategy and motivation was found to be significant (0.003). The findings led to the conclusion that the Talking Stick strategy was successfully to improved students’ speaking skills regardless of their motivation level, and there was a significant interaction between teaching strategy and motivation in influencing speaking outcomes.